THE EFFECT OF TEACHING BY USING INTERACTIVE APPROACH ON READING COMPREHENSION TO THE TENTH GRADE STUDENTS OF MADRASAH ALIYAH SWASTA GP. TEUNGOH KOTA LANGSA - Maria Ulfa (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This research deals with the effect of teaching by using Interactive Approach on the students' reading comprehension. The objective of the study is to investigate the effect of applying Interactive Approach on the students' reading comprehension. The sample of this study was 32 students. This research was conducted with an experimental research. The writer took 1 class of Grade X Students of Madrasah Aliyah Swasta Gp. Teungoh Kota Langsa as the sample and the class was divided into two treatments. The first treatment was the control group and the second treatment was the experimental group. The experimental group was taught by applying Interactive Approach, and the control group was taught by applying Conventional Approach. The instrument for collecting the data was objective test and essay test. To obtain the reliability of the test, the writer used Pearson Product Moment formula. The result of the study showed that the reliability of the test was 0.57. The data were analyzed by using t-test formula. The analysis showed that the scores of the students of the experimental group were significantly higher than the scores of the students in the control group at the level significance 0.05 with the degree of freedom (df) 60 at the level of significance 0.05, it was found out that tobserved value 4.725 > ttable value 3.460. Therefore, the hypothesis that Interactive Approach significantly affects the students' reading comprehension is accepted.